2020
DOI: 10.1002/ejp.1582
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia is a risk factor for spreading of chronic pain: A Swedish longitudinal population study (SwePain)

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This study highlights the coexistence and overlap of mood disorders and insomnia in patients suffering from pain syndromes, which have little or no importance when assessing patients in primary health care centers. Taking note of the underdiagnosis of this overlap, as well as of the expanding anamnesis, and correctly using diagnostic tools for the disorders of interest in this study, which the current literature describes, increases their diagnosis rate by ignoring the positive relationship that exists between these disorders, and ignoring a fundamental pillar in the comprehensive treatment for these patients, in which there is more scientific evidence every day [32][33][34][35][36][37]. Regarding the results obtained, women continue to be the most affected in the development of mental disorders in the course of pain syndromes showed the most affected anatomical areas being the spine and the head.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the coexistence and overlap of mood disorders and insomnia in patients suffering from pain syndromes, which have little or no importance when assessing patients in primary health care centers. Taking note of the underdiagnosis of this overlap, as well as of the expanding anamnesis, and correctly using diagnostic tools for the disorders of interest in this study, which the current literature describes, increases their diagnosis rate by ignoring the positive relationship that exists between these disorders, and ignoring a fundamental pillar in the comprehensive treatment for these patients, in which there is more scientific evidence every day [32][33][34][35][36][37]. Regarding the results obtained, women continue to be the most affected in the development of mental disorders in the course of pain syndromes showed the most affected anatomical areas being the spine and the head.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments such as patient-tailored content or format of ICBT have been studied (Păsărelu et al, 2017) and may be relevant when symptoms vary. Chronic pain patients have a high prevalence of comorbidity, for example, insomnia (Wiklund et al, 2020), depression (Gasslander et al, 2022b), and obesity (Dong et al, 2021). Today, not enough is known about the effects of fitting patients' needs, technology features, and treatment assignments.…”
Section: Future Directionsmentioning
confidence: 99%
“…The relationship between sleep and pain appears to be dose dependent 25,28,29,35,38. An 11-year cohort study of older adults found a dose-dependent and reciprocal relationship between sleep disturbance and persistent pain severity and number of pain sites 29.…”
Section: Relationship Between Sleep and Painmentioning
confidence: 99%